Perineal herniorrhaphy with pedunculated tunica vaginalis communis in dogs: Description of the technique and clinical case series - Heishima, Tatsuya; Asano, Kazushi; Ishigaki, Kumiko; Yoshida, Orie; Sakurai, Naoki; Terai, Kazuyuki; Seki, Mamiko; Teshima, Kenji; Tanaka, Shigeo (Frontiers in Veterinary Science, 2022)
Background: Perineal hernia (PH) in dogs is caused by separation of the anal septal muscles and the displacement of pelvic/abdominal organs under the perineal skin. Reconstruction of the pelvic septum by surgical repositioning is the only curative treatment. Objectives: To describe the procedure and outcomes of surgical repair using the pedunculated tunica vaginalis communis (TVC) for PH in dogs. Methods: Intact male dogs diagnosed with PH were included in this study. For surgery, each dog was positioned in the Trendelenburg position. Castration was performed with the open technique, followed by colopexy and cystopexy via laparotomy. The remaining bilateral TVCs transposed to the opening of PH were used for the perineal herniorrhaphy. Intraoperative findings, complications, and outcomes were evaluated and recorded. Results: Eight dogs (median age 10.5 years [range, 9-13 years]; median body weight 4.9 kg [range, 1.6-12.3 kg]) were treated using the TVC surgical technique. Perineal herniorrhaphy with the TVC was feasible in all dogs. The median operation time was 105.5 mins [range, 46–149 mins] in unilateral PH, whereas the operation time was 92 and 122 mins in two dogs with bilateral PH. Short-term postoperative complications during hospitalization did not occur in six dogs, whereas the residual two dogs had temporary local infection as a minor complication. Postoperative recurrence occurred in one dog (13%) on postoperative day 136. Conclusions: Our study suggests that the herniorrhaphy technique using the pedunculated TVC is an alternative option for repair of PH in dogs.